Scoring Of High Risk Mothers And Related Outcome - Krishnan V; Idris M.Z; Srivastava V.K; Bhushan V; Chandra M.R (Wolters Kluwer Medknow Publications, 1988)
In a study of 777 mothers delivering at Dufferin Hospital, Lucknow, 195 (25.1 %) mothers were in O risk group, 321 (41.3%) in 1-3 risk group, 199(25.6%) in 4-6 risk group and 62 (7.9 %) in risk group 7 +. On the other hand, caesarean section increased from 3(1.5 %) in â€˜Oâ€ risk mothers to 25 (40.4%) in 7 + risk score mothers. The incidence of low birth weight was lowest (5/ 1000 births) when risk score was 0 and highest (432.8 / 1000 births) when risk score was 7 +. Out of a total of 777 mothers, 222 (28.5%) had postnatal complications. In â€˜Oâ€ risk group, out of 195 mothers only 24 (12.3 %) had postnatal complications, while 37 (59.7 %) out of 62 had complications in 7 + group. The maternal mortality rate was 1.3 / 1000 live births. Perinatal mortality rate was 61.6 /1000 total births and neonatal mortality rate was 47.7/1000 live births.